Cellulose/TiO2 Humidity Sensor - Susana Devesa; Zohra Benzarti; Madalena Costa; Diogo Cavaleiro; Pedro Faia; Sandra Carvalho (Sensors)
Resistivity-type humidity sensors, which detect changes in electrical resistance in response to variations in environmental humidity, have garnered significant interest due to their widespread application in industry, agriculture, and daily life. These sensors rely on diverse materials for fabrication, but their increasing variety has contributed to the accumulation of electronic waste. As a biodegradable polymer, cellulose offers unique advantages, including a naturally hydrophilic structure and a large specific surface area. These properties enable cellulose to reduce e-waste generation while facilitating the efficient adsorption of water molecules. However, despite these benefits, humidity sensors based solely on cellulose often suffer from poor sensitivity due to its limited hydrophilicity and non-adjustable structure. To overcome these limitations, the development of composite materials emerges as a promising solution for enhancing the performance of cellulose-based humidity sensors. Combining the complementary properties of cellulose and TiO2, this work presents the development of a cellulose/TiO2 composite humidity sensor through a sustainable approach. The resulting composite material exhibits significantly improved sensitivity compared with a sensor fabricated purely from cellulose. To achieve this, TiO2 nanoparticles were incorporated into cellulose extracted from potato peels, and the composite film was fabricated using the casting method. The sensor’s performance was evaluated by analyzing the dependence of its complex impedance, measured over a frequency range between 2 kHz and 10 MHz, while varying relative humidity (RH).